2013
DOI: 10.1002/acr.21835
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Pediatric Automated Neuropsychological Assessment Metrics in childhood‐onset systemic lupus erythematosus

Abstract: Objective To evaluate the reproducibility and validity of the Pediatric Automated Neuropsychological Assessment Metrics (Ped-ANAM) when used in childhood-onset systemic lupus erythematosus (cSLE). Methods Forty children with cSLE and 40 matched controls were followed for up to 18 months. Formal neuropsychological testing at baseline was repeated after 18 months of follow-up; overall cognitive performance and domain-specific cognition (attention, working memory, processing speed and visuoconstructional abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 34 publications
2
42
0
2
Order By: Relevance
“…Of all of the PedANAM performance parameters, the accuracy score has shown the highest consistency and reliability (16). Additionally, the coefficient of variation of time required for a correct response (CVc) has been proposed as a measure of consistency on the performance of a given PedANAM-subtest (21). …”
Section: Methodsmentioning
confidence: 99%
“…Of all of the PedANAM performance parameters, the accuracy score has shown the highest consistency and reliability (16). Additionally, the coefficient of variation of time required for a correct response (CVc) has been proposed as a measure of consistency on the performance of a given PedANAM-subtest (21). …”
Section: Methodsmentioning
confidence: 99%
“…Reliability coefficients as low as 0.22 have been reported for the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT; ImPACT Applications, Inc, Pittsburgh, PA) 7 and 0.10 for the Automated Neuropsychological Assessment Metrics (ANAM; Vista LifeSciences, Parker, CO). 8 Reliability is an extremely important concept in concussion testing due to individual serial-testing strategies. 9 Reliability refers to the consistency of the scores obtained from a test.…”
mentioning
confidence: 99%
“…18 The controversy of CNT reliability is further complicated because of the wide range of reliability estimates (from as low as 0.10 to as high as 0.93) reported across studies. 7,8,11,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] Because of the conflicting reports, a more thorough investigation of the reliability of CNT scores is necessary. Although a systematic review 10 summarizing the reliability of ImPACT scores has been previously published, this study was limited to a single CNT.…”
mentioning
confidence: 99%
“…7 Paediatric Automated Neuropsychological Assessment Metrics (Ped-ANAM) tasks are automated and various scores are generated for each test to measure patient cognitive ability. We previously showed that of the available Ped-ANAM scores, the a ccuracy score , for example, percentage of correct answers was most affected in patients with cSLE 5…”
Section: Methodsmentioning
confidence: 99%